The Relationship Between Working Environment and Employee Performance - Athirah Saidi, Nur Shifaa; Michael, Florianna Lendai; Sumilan, Helmi; Omar Lim, Sheilla Lim; Jonathan, Victoria; Hamidi, Hana; Abg Ahmad, Abg Izhar (Cognition and Interactive Technologies, 2019)
A positive working environment is vital in ensuring employee productivity to avoid unnecessary stress to the employees thus affecting their work performances. There are several working environment factors that contributed towards job satisfaction. Hence, this study aimed to investigate the relationship between the working environment and employee performance based on five dimensions of the working environment. The quantitative survey design was utilized in this study and data were collected by using questionnaires. The respondents of this study were administrators from different departments in a local municipality located in Kuching. The data were analysed by using Pearson’s Correlation Analysis to measure the relationship between the variables. The finding shows there is a significant relationship between the working environment and employee performance. Support from supervisor was found to be the dominant variables in ensuring a positive working environment. Keywords: Working environment; Employee performance; Municipality; Human resource; Health